Identifying characteristics of parental autonomy support and control in parent–child interactions. Issue 2 (25th January 2021) - Zhang, Heyi; Whitebread, David
ABSTRACT: The importance of parental autonomy support to children's development and learning has been widely studied among Western school-age children, while scant research has been conducted among young children in other cultural contexts. To address this research gap, the primary aim of the present study was to examine the role of parental autonomy support and control in Chinese preschool children's task performance and to describe the characteristics of autonomy-supportive parents and controlling parents in problem-solving interactions. One hundred and two children, aged from 59 to 79 months, participated in the study with their parents. Parental behaviours were video recoded and coded for an in-depth observational analysis. Results indicated that Chinese parents' autonomy support was particularly important as a unique predictor of child-alone task performance, which supported evidence found in Western studies.